Combined Wind Vector and Sea State Impact on Ocean Nadir-Viewing Ku- and C-Band Radar Cross-Sections - Bertrand Chapron; Ngan Tran (Sensors, 2006)
The authors report the first results in studying the polarization anisotropy of themicrowave backscatter from nadir observations provided by Jason-1 altimeter in both Ku-and C-band. A small but clear wind direction signal for wind speeds above 6 m/s is revealed.These azimuthal variations of radar cross-section increase with increasing wind speed up to14 m/s. The signatures then level off at higher winds. These results extend, for the first time,recent theoretical improved scattering approximation, and point some similarities betweenscattering and emission mechanisms at nadir. The observed directional effect can thus beinterpreted as a signature of the curvature anisotropy of wind-generated short-scale waves.Sensitivities to both wind speed and sea state are also reported in the present analysis.